Caracterização genética de duas populações de Rhamdia quelen através da utilização de marcadores microssatélites - Freitas, Suzane Fonseca (2017)
The catfish Rhamdia quelen stands out as a native species of economic interest for the southern region of Brazil, being the same one indicated as promising candidate for insertion in programs of genetic improvement. The success of the implementation of breeding programs is based on the formation of the base population, where one must pay attention to the genetic variability of the breeding stock and which usually come from wild populations. Therefore, the objective of this study was to genetically evaluate two natural populations of catfish from the Mirim and Mangueira lagoons in order to subsidize studies that effectively aim at the genetic improvement of this species. A total of 40 animals were collected from each pond, where two sources of biological material were collected from each fish (fragment of muscle tissue and caudal fin). The extraction of genomic DNA was carried out by means of an in house and low cost genomic DNA extraction protocol in the two target populations, as well as the efficiency of the protocol in the two sources of biological material collected. Eight microsatellite specific loci of the species were selected for PCR amplification, with the criterion of their choice being the existence of a motif of tetranucleotide repeat, following the trend of international forensic analysis (ISFG), which points to the motif as the most robust and reliable for genetic analyzes. The extraction protocol was effective for both sources of biological material, presenting samples with good quality DNA, without indicative of degradation, protein excess or contamination. Likewise, the 8 selected loci amplified for the two study populations, with good quality amplicons, being the same ones suitable for use as a tool in the genetic analysis of catfish, aiming at its improvement.